Manajemen sumber-sumber informasi elektronik (e-resources) di perpustakaan akademik - Ulpah Andayani (Al Maktabah, 2014)
The advancement of technology, the changes of user information behavior and scientific communication patterns among scholars, and the demand of the variety of collections have encouraged academic libraries to re-orientate and re-envision the provision of information resources. Besides printed materials, academic libraries are required to accomodate the information needs by acquiring non printed materials or electronic information resources. The provision of electronic resource, in addition, is aimed to provide a wider access to information. However, the processes and procedures of electronic information resources (e-resources) acquisition are different from printed materials. This paper is to delineate and expound the management of electronic information resources in academic libraries, particulary in terms of the acquisition  and the provision of access to electronic resources.